Group Investigation Learning Model Influence on Prospective Elementary School Teachers’ Democratic Attidudes - Sakinah, Nur; Herwin; Kawuryan, Sekar Purbarini; Bara, Sri Nensi (Universitas Pendidikan Ganesha, 2024)
Generally, the weakness in students' democratic attitudes stems from a lack of understanding of the principles of democracy. Therefore, there is a need for a successful learning model to instill democratic attitudes in students. The purpose of this study is to analyze the impact of the group investigative learning model on the democratic attitudes of Elementary School Education (PGSD) students. A quantitative approach and quasi-experimental design were employed in this study. Employing a random cluster sampling technique for sample selection, the population comprised a total of 71 second-semester elementary education students, divided into classes A2 and A7. Questionnaires, observations, and documentation were used for data collection. Data analysis involved descriptive analysis and inferential analysis, using tests for normality, homogeneity, and hypothesis testing through the independent simple t-test. The data analysis resulted in a significance value (2-tailed) of 0.000, which is less than 0.05 (0.000 < 0.05) in the t-test for the experimental class. Therefore, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted, indicating that the implementation of the group investigative learning model significantly influences students' democratic attitudes.